Debt buildup and currency vulnerability evidence from global markets. - Park, Donghyun (ADB economics working paper series, 2020)
This paper examines how debt buildup is related to currency depreciation pressure. It highlights the importance of a debt surveillance framework that monitors both public and private debt buildup, especially in emerging markets.